Avaliação da albumina modificada pela isquemia na anemia associada à doença renal crônica - Cichota, Luiz Carlos (2007)
Chronic kidney disease (CKD) is highly prevalent, with increasing numbers of patients affected by the disease world-wide, and anemia is a common finding in patients with CKD. Anemia impacts negatively on cardiovascular disease, exercise capacity and quality of life, resulting in a significant mortality and morbidity. The aim of this study was to evaluate the levels of ischemia-modified albumin and lactate in patients with established anemia associated to CKD and its correlations with hemoglobin levels. Hematocrit, hemoglobin, iron, ferritin, albumin, creatinine, lactate and IMA were measured in 17 patients with established anemia associated to CKD and 19 controls by standard methods. The results of hematocrit, hemoglobin, iron and albumin were lower in anemia group than control group. Ferritin, creatinine and lactate levels were higher in anemia of CKD group than control group. IMA increases in anemia group (0.8115 ± 0.1304) ABSU compared to control (0.4951 ± 0.0393) ABSU. Significant correlations between IMA and lactate, IMA and hemoglobin, IMA and creatinine, and hemoglobin and lactate were observed. IMA and lactate increase during anemia and this elevation could be associated to hypoxia due to low hemoglobin levels. However, our data suggest that lactate is more sensitive to detect hypoxia in anemia compared to IMA.